PENGARUH EMPLOYER BRANDING DAN KEPEMIMPINAN TRANSFORMASIONAL TERHADAP RETENSI KARYAWAN - Yustika, Annisa; Siswanti, Yuni; Wahyuni, Purbudi (Gapenas Publisher, 2025)
This study aims to empirically examine the 0069nfluence of employer branding and transformational leadership on employee retention. The research focuses on Waroeng Spesial Sambal “SS,” with the population consisting of all employees of Waroeng SS in the Special Region of Yogyakarta. The sampling technique used is purposive sampling, with 85 respondents. Data analysis is conducted using SEM-PLS with SmartPLS 4.0 as the analytical tool. The results indicate that employer branding has a significant impact on employee retention. Furthermore, the findings confirm that transformational leadership has a significant impact employee retention. The implications of this study suggest that Waroeng SS management should enhance the facilities and branding offered to employees, as what the company provides can significantly influence employees’ decision to remain with the organization